2012
DOI: 10.1016/j.jvs.2011.09.004
|View full text |Cite
|
Sign up to set email alerts
|

A phase II dose-ranging study of the phosphodiesterase inhibitor K-134 in patients with peripheral artery disease and claudication

Abstract: K-134 was generally well tolerated. K-134 at a dose of 100 mg twice daily did not affect PWT according to the primary analysis, but K-134 and cilostazol both increased PWT when analyzed using a mixed-effects model and in the per-protocol population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 19 publications
1
16
1
Order By: Relevance
“…Although the safety of treadmill testing has not been evaluated extensively in the PAD population, 1 study included comprehensive hemodynamic and ECG monitoring during exercise in a large cohort and identified no safety concerns, including no changes indicative of cardiac ischemia during testing. 37 This finding is consistent with the reported adverse event experience from clinical trials using peak treadmill testing involving thousands of patients with PAD. However, most patients with PAD have underlying coronary artery disease; therefore, ECG monitoring during all peak treadmill exercise tests in this population is recommended to enhance patient safety.…”
Section: Conduct Of the Exercise Testsupporting
confidence: 84%
See 2 more Smart Citations
“…Although the safety of treadmill testing has not been evaluated extensively in the PAD population, 1 study included comprehensive hemodynamic and ECG monitoring during exercise in a large cohort and identified no safety concerns, including no changes indicative of cardiac ischemia during testing. 37 This finding is consistent with the reported adverse event experience from clinical trials using peak treadmill testing involving thousands of patients with PAD. However, most patients with PAD have underlying coronary artery disease; therefore, ECG monitoring during all peak treadmill exercise tests in this population is recommended to enhance patient safety.…”
Section: Conduct Of the Exercise Testsupporting
confidence: 84%
“…45,46 and a variety of medications. 26,37,44,47 The treadmill has been used in several drug trials of agents, including those with small effect sizes. For example, a meta-analysis of propionyl-L-carnitine demonstrated an effect size in a range of 0.11 to 0.22, whereas phosphodiesterase-3 inhibitors have effect size estimates in the range of 0.28 to 0.32.…”
Section: Treadmill Reliabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…65 The efficacy signals from 2 additional phosphodiesterase type 3 inhibitors support a disease benefit for the class, albeit one that is not completely understood. 66,67 Older medications, such as pentoxifylline and naftidrofuryl, are approved for use in patients with PAD within and outside of the United States, respectively. The overall data supporting any functional benefit for treatment of patients with PAD with pentoxifylline are weak.…”
Section: Existing Medical Therapy For the Exercise Limitation In Padmentioning
confidence: 99%
“…In contrast, anti-platelet activities of K-134 are more potent than cilostazol. K-134 is currently being developed for treating intermittent claudication associated with peripheral arterial diseases [14] and the beneficial effects of PDE3 inhibitors on peripheral arterial disease are attributable to not only antiplatelet activity but also vasodilatory activity or some chronic unknown effects [11], [13], as no studies have shown a benefit of other antiplatelet drugs such as acetylsalicylic acid and clopidogrel [15]. Meanwhile, the potent anti-platelet activity of K-134 also make it a potential alternative agent for preventing secondary cerebral infarction because antiplatelet therapy for secondary stroke prevention has been proved to be beneficial in clinical trials [3].…”
Section: Discussionmentioning
confidence: 99%